2020
DOI: 10.3934/publichealth.2020041
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle management of polycystic ovary syndrome: a single-center study in Bosnia and Herzegovina

Abstract: Background Polycystic ovary syndrome (PCOS) is a complex endocrinopathy affecting up to 20% of pre-menopausal women. The most recent international guidelines set lifestyle management as the cornerstone of the PCOS treatment. Still, there is a paucity of data on the implementation of lifestyle management in clinical practice. This cross-sectional study aimed to explore physicians-reported practices in PCOS lifestyle management in the Sarajevo Canton, Bosnia and Herzegovina (BiH). The profession of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In addition, studies have also confirmed that the pregnancy rate of PCOS patients is significantly higher after lifestyle management, and depression, anxiety and stress are also improved [ 6 , 15 ]. Although there have been researches on PCOS lifestyle management, the research to date has tended to focus on the overall impact of different diets, exercise types and/or compliance on PCOS patients rather than health behavior subtypes [ 15 , 16 ]. Due to the individuals differences and heterogeneity, the rationality and scientificity of using the same intervention method remains to be studied, as they may require different lifestyle management and have different consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have also confirmed that the pregnancy rate of PCOS patients is significantly higher after lifestyle management, and depression, anxiety and stress are also improved [ 6 , 15 ]. Although there have been researches on PCOS lifestyle management, the research to date has tended to focus on the overall impact of different diets, exercise types and/or compliance on PCOS patients rather than health behavior subtypes [ 15 , 16 ]. Due to the individuals differences and heterogeneity, the rationality and scientificity of using the same intervention method remains to be studied, as they may require different lifestyle management and have different consequences.…”
Section: Introductionmentioning
confidence: 99%